Paradigmas de qualidade regulatória e estratégias de melhora regulatória (better regulation) na Europa e no Brasil - Francisco, Felipe Ferreira (2021)
This dissertation will discuss the emergence of the regulatory state in Brazil from the 1990s onwards and will verify the existence of Better Regulation policies for regulatory improvement in Brazil, similar to the European model. Better Regulation policies are understood as second-order regulatory policies designed to incentive the regulatory quality and the continuous improvement of the regulation. To support this discussion, regulatory quality paradigms will be presented, which are the foundations of Better Regulation programs and their regulatory toolbox: (i) impact analysis, (ii) strategic planning, (iii) stakeholder consultation and participation, (iv) simplification and cost reduction; (v) regulatory supervision, and (vi) evaluation and monitoring. The history and current context the Better Regulation initiative in the European community will be presented, as its actual guidelines. The European model is currently complete, comprising a sophisticated and reflexive set of such tools. In Brazil, the emergence of the regulatory state was based on the legally reinforced autonomy granted to federal authorities based on intelligible standards and principles. This model sought to ensure these special autonomous decision-making, functional, administrative and financial powers, however it indeed seems incomplete and fragile in the face of political pressure and influences. It will be demonstrated that, different from the model of European regulation, the emergence of independent regulatory entities was not accompanied by policies that encourage the regulatory quality and improvement of these regulatory entities, in spite of substantive recent progresses.